Pengaruh Ketepatan Anggaran, Sistem Pengendalian Manajerial Sektor Publik, dan Sistem Pelaporan Terhadap Akuntabilitas Kinerja - Rininda, Bella Puspita; Sudaryati, Erina (E-Jurnal Akuntansi; Vol 30 No 5 (2020)DO - 10.24843/EJA.2020.v30.i05.p03, 2020)
The purpose of this research is to examine and analyze the influence of the precision it managerial control systems, public sector, and reporting systems that allegedly influenced the performance accountability. The sample of this research was an employee of SKPD Tanah Laut Regency selected by using Purposive Sampling method with the total number of respondents as many as 81 people. The data collection of this research is used the questionnaires instrument. The data collected was analyzed by multiple linear regression analysis. The results of this research indicate that the accuracy and control systems of managerial accountability to public sector performance. However, the reporting system does not influence on performance accountability in SKPD Tanah Laut Regency. Keywords: Accountability For Performance; It Managerial Control Systems; The Accuracy Of The Public Sector; The Reporting System.